2017
DOI: 10.1002/aelm.201700141
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Physical and Electronic Properties of GeSe for Photovoltaic Applications

Abstract: GeSe is a promising absorber material for photovoltaic applications due to its attractive material, optical, and electrical properties as well as its low toxicity and earth abundance. The first GeSe‐based solar cell with 1.48% efficiency has been recently reported through self‐regulated rapid thermal sublimation. However, most of the fundamental physical and electronic properties of GeSe such as refractive index, dielectric constant, carrier mobility, lifetime, and diffusion length remain unclear, despite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 48 publications
4
82
0
4
Order By: Relevance
“…Our calculated band structure (green lines) was in good consistence with the experimental result measured by ARPES. From the calculated band structure shown in Figure d, it can be observed that GeSe displayed an indirect bandgap of 1.13 eV, close to the previous experimental values . The anisotropic electronic structure of GeSe can be further confirmed by the constant energy contours (CECS) measured by ARPES.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Our calculated band structure (green lines) was in good consistence with the experimental result measured by ARPES. From the calculated band structure shown in Figure d, it can be observed that GeSe displayed an indirect bandgap of 1.13 eV, close to the previous experimental values . The anisotropic electronic structure of GeSe can be further confirmed by the constant energy contours (CECS) measured by ARPES.…”
Section: Resultssupporting
confidence: 84%
“…As an isostructural analogue of BP, GeSe also possesses the unique in‐plane anisotropic crystal structure stemmed from its puckered atom structure with two nonequivalent in‐plane crystal directions: armchair and zigzag . With a suitable bandgap (1.14 eV), high absorption coefficient (>10 5 cm −1 ), and high carrier mobility (128.6 cm 2 V −1 s −1 ), GeSe has demonstrated a promising potential in thin‐film solar cells and exhibited an efficiency of 1.48% with good stability . Simultaneously, several theoretical calculations have predicted that the efficiency of GeSe solar cells can be further promoted to as high as ≈18% .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, SWNT films, which exhibit full solar spectrum absorption capability, are considered as ideal candidates of ultrathin photothermal material for efficient solar steam generation. More importantly, the SWNT film with porous network structure and superior mechanical strength shows great potential to combine with other photothermal materials such as MoS 2 , noble metal nanoparticles, PPy, graphene, or solar energy harvesting films to obtain a hybrid solar steam generation film with synergistic photothermal properties.…”
Section: Introductionmentioning
confidence: 91%
“…As a member of group‐IV monochalcogenides, GeSe has been considered as a promising absorber material for photovoltaic applications due to its attractive optical and electrical properties as well as earth‐abundant and low‐toxic constituents . Recently, GeSe solar cell with an efficiency of 1.48% fabricated through self‐regulated rapid thermal sublimation (RTS) was first reported by our group, demonstrating the potential of GeSe for solar cells.…”
mentioning
confidence: 99%
“…Bandgaps of our four samples were further estimated by plotting ( αhν ) 1/2 versus ( hν ), where α is the absorption coefficient shown in Figure S8, Supporting Information (calculated based on the simplified formula: α = d −1 ln( T −1 ), where T is the transmittance and d is the thickness of GeSe film, identical to the thickness in Figure S7, Supporting Information) and hν is the photon energy, as shown in Figure b. The bandgap of as‐prepared amorphous GeSe film was found to be 1.79 eV, while the bandgap of the sample annealed at 500 °C was about 1.14 eV, in good agreement with the values from literatures and our previous reports . It was noteworthy that GeSe films annealed at 350 and 400 °C with corresponding GeSe nanosheets thickness of 2.5 and 4.5 nm showed bandgaps of 1.44 and 1.20 eV, respectively.…”
mentioning
confidence: 99%